Imogene King's Interacting Systems Theory: Application in Emergency and Rural Nursing - Leigh Ann Williams (Rural Nurse Organization; Binghamton University, 2001)
Imogene King is a nursing theorist who has made significant contributions to the development of nursing knowledge. This paper gives an overview of King's Conceptual Framework and Theory of Goal Attainment and applies the theory to emergency and rural nursing. While all of King's concepts may not be applicable to emergency and rural nursing, applicable concepts are discussed. Specific clinical examples are presented to support King's work in practice. The concepts of self, body image, growth and development, time, communication, and interaction are the concepts from King's theory that the author identifies as being most useful when working with clients in the emergency room and in the rural environment. Keywords: rural health, inclusion, children, special health care needs http://dx.doi.org/10.14574/ojrnhc.v2i1.477